NEW METABOLIC INDEX USE POTENTIALITIES IN EVALUATION OF INSULIN RESISTANCE IN CLINICAL PRACTICE - G. E. Roytberg; J. V. Dorosh; O. O. Sharkhun; T. I. Ushakova; E. A. Trubino (Столичная издательская компания, 2015)
Early diagnostics of insulin resistance (IR) is one of the methods of primary prevention of cardio-vascular diseases and type 2 diabetes mellitus. The HOMA-IR index and ratio of plasma triglyceride to high-density lipoprotein cholesterol concentration are the most frequently used indices in clinical and epidemiological scientific research. Prognostic value and efficacy of these tests as a screening method are not high. What method of IR detection should be used in clinical practice and how to interpret received values of the indices is still a matter of dispute. Aim. To evaluate informative value, sensitivity and specificity of a new metabolic index (MI) for IR estimation in comparison with the calculated HOMA-IR index. Material and methods. A total of 845 patients (298 men, 547 women) were enrolled into the further study after an outpatient regular medical check-up of 2,615 persons. Mean age of the patients was 45.77±12.18 years, body mass index - 28.95±1.44 kg/m2. To evaluate lipid and carbohydrate metabolism blood chemistry parameters were assessed. IR was determined by the Homeostasis Model Assessment (HOMA-IR) and an oblique calculated index based on lipid metabolism parameters. In accordance with the developed screening method of IR detection (invention patent № 2493566) MI considering carbohydrate and lipid changes was proposed. Results. Calculation of MI and its threshold level was performed by analysis of a characteristic curve. Graphical dependence between sensitivity and specificity of the proposed index was demonstrated: sensitivity of the test was 75.7%, specificity - 89.1%. Probability of IR at MI value >7.0 was 63.5% (positive predictive value), probability of IR absence at the index value ≤7.0 was 93.6% (negative predictive value). The general accuracy of the test, which is characterized by the area under the characteristic curve, was 0.881 with 95%-confidence interval within 0.854-0.905. Conclusion. The importance of negative result - absence of IR at normal values of MI and use of routine blood chemistry parameters for its calculation allows to recommend MI for IR screening in clinical practice. Distinction of the proposed method of IR diagnostics from the other known oblique laboratory methods is in easy calculation based on the routine biochemistry parameters detected in venous blood on one occasion. Use of the proposed MI allows to economically and efficiently estimate indirectly sensitivity to insulin without additional assessment of laboratory indices.